The role of gut microbiota in the development and management of Type 2 diabetes: Insights into the gut-pancreas axis and its potential for therapeutic interventions - Wareesha Bint E Fayyaz, Dr. Amna Rauf, Vibhor Barve, Haresh Kumar, Dr Rohait Kumar, Muhammad Usman, Muhammad Hamza Javaid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: T2D also known as Non-Insulin Dependent Diabetes mellitus (NIDDM) is a common endocrine disorder of insulin resistance and reduced glucose removal by pancreatic β-cells. Recent studies show that gut microbiota play a vital part in the pathogenesis of T2D. Gibson et al., pointed that dysbiosis, a disruption in the composition of the gut microbiota can affect insulin sensitivity glucose homeostasis and pancreatic function in several ways as through inflammation and the microbial metabolite signals. Aim: This research will seek to determine the relationship between gut microbiota and T2D with keen interest on the gut-pancreas axis and the treatment possibilities under microbiota intervention. Methods: A systematic analysis of published papers in Medline and Cochrane involving clinical trials and cross-sectional studies was carried out and 16S rRNA sequencing, metagenomic, and metabolic analysis including fasting blood glucose and insulin resistance assessment were also performed for the confirmation of the findings. Possible relationships of gut microbiota with T2D were explored and compared with the existing treatment modalities including probiotics, prebiotics, and metformin and others.